Dampak Interaksi Liabilitas terhadap Profitabilitas sebelum dan ketika Covid-19 pada Perusahaan Perbankan di Indonesia - Yunina, Fitri; Maidar; Manuru, Hernata Br. (Jurnal EMT KITA, 2024)
This research aims to analyze the impact of interactions between liabilities, both short and long-term, on the profitability of banking companies in Indonesia before and during the Covid-19 pandemic. A quantitative approach is used using secondary data from pooled data or time series. The research sample consisted of 32 companies, with an observation period of 3 years, thus covering 96 observations as research objects. Analysis of research results, both partially and simultaneously, shows that short-term liabilities and long-term liabilities have a significant influence on the profitability of banking companies. These findings contribute to the understanding of the relationship between liability structure and financial performance of banking companies, especially in facing the economic challenges caused by the global pandemic.